2021
DOI: 10.21203/rs.3.rs-514975/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated With An Interruption in Treatment of People Living With HIV in USAID-Supported States in Nigeria: A Retrospective Study From 2000‒2020

Abstract: Background: Patient interruption of antiretroviral therapy (ART) continues to limit HIV programs’ progress toward epidemic control. Multiple factors have been associated with program interruptions in treatment (IIT)—also referred to by the World Health Organization as loss to follow-up (LTFU)―including age, gender, CD4 count, and education level. Program implementers can prevent future IIT by understanding which clients are more likely to interrupt treatment. In this paper, we explore the factors associated wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Our study found that adults in second-line ART regimens had a higher risk of LTFU than those in the rstline. Our nding is similar to the studies conducted in Nigeria [19][20] and Uganda [24], which reported a high risk of LTFU in treatment among patients on a second-line regimen. However, the nding is inconsistent with a study [31,36] that found patients on 1st line regimens too have an increased risk of LTFU.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found that adults in second-line ART regimens had a higher risk of LTFU than those in the rstline. Our nding is similar to the studies conducted in Nigeria [19][20] and Uganda [24], which reported a high risk of LTFU in treatment among patients on a second-line regimen. However, the nding is inconsistent with a study [31,36] that found patients on 1st line regimens too have an increased risk of LTFU.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of LTFU in adults PLHIV in the current study was similar to the ndings of studies conducted in Nigeria and Gabon, where the cumulative rate of LTFU at 13-and 10-years review in Nigeria was 30.6% and 32% [19,20], while in Gabon in a two years review was 34.1% [21]. The study ndings are in contrast to the 13.45% LTFU in a retrospective study in Northwest Ethiopia [22], 3% LTFU in a study in French [23], 12.75% LTFU in a retrospective study in Kampala-Uganda [24], 12.8% LTFU in a cohort study in South Africa [25], while a study done in Guinea and Kenya reported a prevalence of 57.61% and 54% LTFU from a seven years follow-up study [26,27].…”
Section: Discussionsupporting
confidence: 87%